Social Resistance to the Hydrological Transition in Southern Spain: Public Support for the Building of New Reservoirs - Regina Lafuente; Ernesto Ganuza; Pilar Paneque (Resources, 2020)
Spain has the most reservoirs in Europe, and is near the top of the list globally. Despite this, national hydrological planning still continues to rely overwhelmingly on this type of infrastructure. This indicates that the traditional hydraulic paradigm is deeply entrenched in Spain. The present work takes the new, hitherto unexplored perspective of public resistance, and seeks to complement other studies by aiming to understand why a hydrological transition, in line with environmental demands, has not taken place in Spain. In order to do this, we analyze data from a representative survey (years 2004–2013) of the residents of one of Spain’s most densely regulated drainage basins, that of the Guadalquivir River. Our results reveal that during a several drought (2005–2008), people’s support for the construction of new reservoirs declined sharply, whilst social resistance to changes in the water management strategy was associated with profiles closest to the agricultural sectorm and characterized by a lack of awareness about water distribution in productive sectors